Review Authorized Biography Angela Merkel - Marieke Oprel (European Journal of Life Writing, 2014)
With Angela Merkel favoured to win the German election again, several political books about the German chancellor were published during 2013. Both in Germany and abroad, observers puzzled over the reasons for the on-going success of Mrs. Merkel, the scientist from East Berlin who became an internationally honoured stateswoman. One book stood out because of the label ‘authorized biography’ on the cover: Angela Merkel. The Chancellor and her world, written by Stefan Kornelius. Whether Merkel asked Kornelius, head of the international section of the Süddeutsche Zeitung, to write a book about her political career and vision, or just commented and approved a book Kornelius had written independently, is not mentioned. However, the fact is that Kornelius’ book is the first biography for which Merkel gave her consent. The question is: what new light does this authorized biography shed on the person behind the politician?